2002
DOI: 10.1007/s00018-002-8527-2
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of poly(ADP-ribose)polymerase 1 as novel coactivator of NF-κB in inflammatory disorders

Abstract: Mammalian poly(ADP-ribose)polymerase 1 (PARP-1) is an abundant nuclear chromatin-associated protein and belongs to a large family of enzymes that catalyzes the transfer of ADP-ribose units from its substrate beta-nicotinamide adenine dinucleotide (NAD+) covalently to itself and other nuclear chromatin-associated proteins. PARP-1 knockout mice are protected against myocardial infarction, streptozotocin-induced diabetes, lipopolysaccharide-induced septic shock, and zymosan-induced multiple organ failure, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
334
1
12

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(361 citation statements)
references
References 202 publications
10
334
1
12
Order By: Relevance
“…Because the ZF DNA binding domain is required for KLF8 interaction with both importin-␤ and PARP-1, it is also possible that PARP-1 relays KLF8 from the importin and helps send KLF8 to promoter DNA of target genes in the nucleus. PARP-1 has been suggested to function as a bona fide transcriptional co-activator, as in the case of PARP-1 regulation of NF B-mediated transcription (26). In contrast, our results show that PARP-1 does not stay together with KLF8 at the promoter of cyclin D1, suggesting that PARP-1 likely works as a messenger to pass KLF8 from the nuclear importin to another co-activator, such as the histone acetyltransferases p300 and p300/CBP-associated factor transcription (11), at the promoter and lets the latter do the job of transcriptional co-activation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ZF DNA binding domain is required for KLF8 interaction with both importin-␤ and PARP-1, it is also possible that PARP-1 relays KLF8 from the importin and helps send KLF8 to promoter DNA of target genes in the nucleus. PARP-1 has been suggested to function as a bona fide transcriptional co-activator, as in the case of PARP-1 regulation of NF B-mediated transcription (26). In contrast, our results show that PARP-1 does not stay together with KLF8 at the promoter of cyclin D1, suggesting that PARP-1 likely works as a messenger to pass KLF8 from the nuclear importin to another co-activator, such as the histone acetyltransferases p300 and p300/CBP-associated factor transcription (11), at the promoter and lets the latter do the job of transcriptional co-activation.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are thought to be related to the inflammation process. Poly-ADP ribosyltransferase-1 was reported as a transcriptional coactivator of NF-κB, an important transcription factor in inflammation [22]. Recently, Van Gool et al [23] reported that intracellular NAD levels positively regulate TNF-α biosynthesis through sirtuin-6; the study was performed using monocytes and showed effects at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…22,213,214 PARP-1 interacts with NF-B, AP-1, and other proinflammatory transcription factors. [215][216][217] PARP-1 enzymatic activity is required for NF-B-mediated gene transcription and for many of the inflammatory responses in microglia. 22,214,218,219 Several PARP inhibitors are now commercially available.…”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%